Characteristics and performance of aerobic granular sludge for domestic wastewater treatment at 30°C - Abdul Jamal, Nur Syahida (2014)
This study investigates the formation of AGS for domestic wastewater treatment applications in hot climate and low humidity conditions (e.g. Arab Saudi) as well as to characterize its performance in removal of nutrients and organic matter. AGS (seeded with domestic sludge from Al-Madina Wastewater Treatment Plant and fed with synthetic wastewater) with an organic loading rate (OLR) of 1.6 kg COD m3d was successfully cultivated with average size of 1-2 mm in lab scaled SBR operated at 30 days with complete cycle time of 3 h at 30 ± 1°C. Results shown the AGS formed had excellent settling ability (average diameter settling velocity, and MLSS) and exceptional performance in COD and nutrient removal with removal efficiency more than 90%.